2010
DOI: 10.1007/s10608-010-9316-0
|View full text |Cite
|
Sign up to set email alerts
|

Does Rumination Predict the Strength of Maladaptive Self-Beliefs Characteristic of Social Anxiety Over Time?

Abstract: Two important components of the Clark and Wells (in Social phobia: diagnosis, assessment, and treatment. Guilford, New York, pp 69-93, 1995) model of social phobia are ruminative processing and maladaptive self-beliefs (high standard, conditional and unconditional beliefs). In a longitudinal design, we hypothesised that rumination at Time 1 would be positively associated with the strength of each of the belief types at Time 2 (while controlling for depression, general anxiety, social anxiety and strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Similar to the results of HSs and CBs, the findings from cross‐sectional studies on UBs (Heeren et al, ; Holzman et al, ; Wong & Moulds, , , , ; Wong et al, , ) indicated positive and significant correlations with measures of social anxiety (Table ). Correlation coefficients were moderate to large and ranged between .41 and .62 with the exception of Heeren et al (), who found small, but significant, correlations with the FNE ( r = .13, p < .01) and the LSAS ( r = .15, p < .01).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Similar to the results of HSs and CBs, the findings from cross‐sectional studies on UBs (Heeren et al, ; Holzman et al, ; Wong & Moulds, , , , ; Wong et al, , ) indicated positive and significant correlations with measures of social anxiety (Table ). Correlation coefficients were moderate to large and ranged between .41 and .62 with the exception of Heeren et al (), who found small, but significant, correlations with the FNE ( r = .13, p < .01) and the LSAS ( r = .15, p < .01).…”
Section: Resultssupporting
confidence: 71%
“…All correlations were based on cross‐sectional data from nonclinical samples, except one study that recruited people that scored high and low on the FNE scale (Wong & Moulds, ). The studies (Heeren et al, ; Holzman et al, ; Wong & Moulds, , , , ; Wong et al, , ) showed that HSs positively and significantly correlated with measures of social anxiety (Table ). Correlation coefficients were moderate to large and ranged between .37 and .65 with the exception of one study (Heeren et al, ), which found a relatively small, but significant, correlation ( r = .17) with the LSAS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high and low socially anxious participants rated their speech performance more favourably following rumination relative to the distraction condition, showing some beneficial effects of anticipatory processing. Whilst this and similar research (e.g., Vassilopoulos 2004Vassilopoulos , 2005Wong and Moulds 2009, 2012a has provided important insights into the consequences of pre-event negative rumination, there is a lack of research investigating the predictors of pre-event rumination.…”
Section: Introductionmentioning
confidence: 96%
“…For example, evidence relates rumination to depression and episodes of major depression, 5 symptoms of anxiety, 5 social anxiety, 6 generalized anxiety disorder, 5 trauma, stress-related disorders, and suicidal ideation. 7 Furthermore, high levels of rumination are associated with low self-esteem and predict excessive alcohol consumption, as well as symptoms of alcohol abuse in the long term.…”
Section: Introductionmentioning
confidence: 99%